Timing and Spectrum of Neurological Complications After Flow Diverter Implantation for Intracranial Aneurysms - Charbonnier, Guillaume; Desilles, Jean-Philippe; Escalard, Simon; Maier, Benjamin; Ciccio, Gabriele; Smajda, Stanislas; Fahed, Robert; Delvoye, François; Redjem, Hocine; Blanc, Raphaël; Piotin, Michel; Mazighi, Mikael (Frontiers in Neurology, 2021)
Background and Purpose The aim of this study was to characterize neurological complications after flow diverter (FD) treatment on a long follow-up cohort and identify predictive factors associated with these complications. Methods This study was conducted on a monocentric cohort of patients treated for intracranial aneurysms by FD. Results Between September 2008 and July 2018, 413 patients were treated for 514 aneurysms: 18% of the patients presented with at least one neurological complication during a median follow-up of 446 days (IQR 186- 1210). Sixty-one patients presented with ischemic complications, 13 with hemorrhagic ones and 10 with compressive processes. Among 89 neurological complications 64.5% were peri-operative (occurring within the 30 days following the procedure) and 35.5% were delayed after one month. Conclusions Overall, neurological complications after FD implantation were overrepresented by cerebrovascular ischemic events occurring during the peri-operative period, but also in a delayed manner after one year. Long-term follow-up is relevant after aneurysm intervention using FD.